Aspectos relacionados à hesitação vacinal: uma investigação à luz dos princípios de marketing social - Brito, Leandro Alves de (2023)
The main objective of this dissertation is to identify which behavioral aspects are related to vaccine hesitation against COVID-19 in the light of social marketing. It is a research of qualitative nature. To obtain the data, interviews were applied with the elaboration of a semi-structured script, where ten people who were interviewed expressed the behavior of vaccine hesitation. The data obtained from the application of questionnaires were categorized according to content analysis of Bardin. The categories of this study were defined a priori, with the three established categories corresponding to the three specific objectives of this research and the subcategories corresponding to the questions of the interview script. The results obtained showed that among the respondents the perception that the pandemic was not severe possibly had implications on the behavior of vaccine hesitancy toward the COVID-19 vaccine. The data obtained from the survey indicates that the main reasons for vaccine hesitancy among respondents are lack of confidence in the efficacy of the vaccine, concern about possible health problems the vaccine could cause, and, in a lower incidence, the cultural, religious, or political influence. Finally, the research highlights the need for social marketing programs and campaigns to overcome vaccine hesitancy in the Brazilian context, given the untapped potential of this approach.